The International Co-Founded/Co-Developed University Model: Considerations for Higher Education Providers - Yenmee, Kik; Mongkhonvanit, Jomphong (Scholar: Human Sciences, 2021)
This case study explores the essential considerations for decision-makers investigating the establishment of co-founded/co-developed universities, including the factors supporting and hindering these decisions. The study also investigates the decision-making phases undergone by higher learning institutions when exploring the potential to establish an international co-founded or co-developed university. Face-to-face interviews were conducted with university leaders, faculty members, and key experts to gain more insights into this decision-making process. A total of 13 participants from three institutions were interviewed. Data analysis guided by the research objectives used the Braun and Clarke’s (2006) six-step coding process for thematic analysis. The findings reveal the following decision-making phases: (1) Considerations, goals, and motivations; (2) Support Collection; (3) Opportunity recognition; (4) Screening, decision-making, and planning; and (5) Operationalization (including finalizing academic programs, selecting faculty and staff, and preparation of buildings and support structures). The findings also reveal that the primary considerations during the decision-making process are issues of finance and quality. Other considerations were around ancillary factors, including political stability, market demand, protection of reputation, and staff safety. Other concerns included support availability, the current position of the institution, government regulations, infrastructure, economic issues, business environment, and the corporate culture of the host nation.